Eliminating Race Differences in School Attainment and Labor Market Success - Keane, Michael P.; Wolpin, Kenneth I. (Journal of Labor Economics, 2000)
In this article, we provide quantitative evidence on the effects of monetary incentive schemes designed to reduce racial differences in school attainment and earnings. Our analysis is based on the structural estimation of a dynamic model of schooling, work, and occupational choice decisions over the life cycle. We consider two recent proposals that, although not specifically targeted to blacks, can be expected to have differential racial impacts. One proposal, suggested by Robert Reich, provides a high school graduation bonus to youths from lower‐income families. The other, suggested by Edmund Phelps, provides wage subsidies to low‐wage workers.